An ab initio study of the electronic structure and optical properties of CdS1-xTex alloys - Yarub, Al - Douri; Ali Hussain, Reshak, Prof. Dr.; H., Baaziz; Z., Charifi; R., Khenata; S., Ahmad; Uda, Hashim, Prof. Dr. (Elsevier Ltd., 2011)
Link to publisher's homepage at www.elsevier.com